Trade-offs between time, predation risk and life history, and their implications for biogeography: a systems modelling approach with a primate case study - Bettridge, C; Lehmann, J; Dunbar, R (Elsevier, 2010)
Group sizes are often considered to be the result of a trade-off between predation risk and the costs of feeding competition. We develop a model to explore the interaction between different ecological constraints on group sizes, using a primate (baboons) case study. The model uses climatic correlates of time budgets to predict maximum ecologically tolerable group size, and climatic predictors of predation risk (reflected mainly in predator density and female body mass) to predict minimum tolerable group size for any given habitat. As well as defining the range of sustainable group sizes for a given habitat, the model also allows us to reliably predict our exemplar taxon's biogeographical distribution across Africa. We also explore the life history implications of the model to ask whether baboons form group sizes which maximise survival or fecundity in the classic trade off between these two key life history variables. Our results indicate that, within the range of study sites in our sample, baboons prefer to maximise fecundity. However, the data indicate that in higher predation risk habitats they would switch to maximising survival at the expense of fecundity. We argue that this is due to the fact that interbirth interval and developmental rates have a ceiling that cannot be breached. Thus, while females can shorten interbirth intervals to compensate for increased predation risk, there is a limit to how much these life history variables can be altered, and when this is reached the best strategy is to maximise survivorship.